A very rare case of extranodal B-cell non-Hodgkin lymphoma presenting with adrenal and heart involvement. (2022) - Papanastasiou, Labrini; Skarakis, Nikitas; Vardaka, Maria; Dimitriadi, Anastasia; Lampropoulou, Pinelopi; Perpinia, Anastasia; Vidalakis, Eleftherios; Choreftaki, Theodosia; Marinakis, Theodoros; Kounadi, Theodora; Vatalas, Ioannis-Anastasios; Michalis, Eurydiki
Abstract: We report an extremely rare case of extranodal B-cell NHL: DLBCL (diffuse large B-cell non-Hodgkin lymphoma), stage IVE, presenting with heart and bilateral adrenal involvement. On admission, adrenal and thorax imaging identified large bilateral adrenal masses and a 4.6 cm mass in the right atrium wall. An adrenal biopsy revealed the presence of a DLBCL, with triple expression of bcl2, bcl6, C-MYC(+70%). Following six cycles of systemic immunochemotherapy with R-DA-EPOCH, and high methotrexate dose for CNS prophylaxis a marked decrease of lymphoma infiltration was observed. The selection of the appropriate treatment modality can lead to profound response and improve patient's outcome.